Sequencing directly from clinical specimens reveals genetic variations in HCMV-encoded chemokine receptor us28 that may influence antibody levels and interactions with human chemokines - Waters, Shelley; Agostino, Mark; Lee, S.; Ariyanto, I.; Kresoje, N.; Leary, S.; Munyard, Kylie; Gaudieri, S.; Gaff, J.; Irish, A.; Keil, A.D.; Price, Patricia; et al. (AMER SOC MICROBIOLOGY, 2021)
Human cytomegalovirus (HCMV) is a beta-herpesvirus carried by;80% of the world’s population. Acute infections are asymptomatic in healthy individuals but generate diverse syndromes in neonates, solid organ transplant recipients, and HIV-infected individuals. The HCMV gene US28 encodes a homolog of a human chemokine receptor that is able to bind several chemokines and HIV gp120. Deep sequencing technologies were used to sequence US28 directly from 60 clinical samples from Indonesian HIV patients and Australian renal transplant recipients, healthy adults, and neonates. Molecular modeling approaches were used to predict whether nine nonsynonymous mutations in US28 may alter protein binding to a panel of six chemokines and two variants of HIV gp120. Ninety-two percent of samples contained more than one variant of HCMV, as defined by at least one nonsynonymous mutation. Carriage of these variants differed between neonates and adults, Australian and Indonesian samples, and saliva samples and blood leukocytes. Two nonsynonymous mutations (N170D and R267K) were associated with increased levels of immediate early protein 1 (IE-1) and glycoprotein B (gB) HCMV-reactive antibodies, suggesting a higher viral burden. Seven of the nine mutations were predicted to alter binding of at least one ligand. Overall, HCMV variants are common in all populations and have the potential to affect US28 interactions with human chemokines and/or gp120 and alter responses to the virus. The findings relied on deep sequencing technologies applied directly to clinical samples, so the variants exist in vivo. IMPORTANCE Human cytomegalovirus (HCMV) is a common viral pathogen of solid organ transplant recipients, neonates, and HIV-infected individuals. HCMV encodes homologs of several host genes with the potential to influence viral persistence and/ or pathogenesis. Here, we present deep sequencing of an HCMV chemokine receptor homolog, US28, acquired directly from clinical specimens. Carriage of these variants differed between patient groups and was associated with different levels of circulating HCMV-reactive antibodies. These features are consistent with a role for US28 in HCMV persistence and pathogenesis. This was supported by in silico analyses of the variant sequences demonstrating altered ligand-binding profiles. The data delineate a novel approach to understanding the pathogenesis of HCMV and may impact the development of an effective vaccine.